A Human Capability Perspective on the Progression of Low-SES Students to Higher Education in Ireland and the UK - Cliona Hannon (MDPI AG, 2023)
This article focuses on targeted programs for low-SES students in two selective universities: Trinity College Dublin, the University of Dublin, Ireland (Trinity Access Programmes/TAP) and the University of Oxford, UK (Lady Margaret Hall Foundation Year/LMH FY). The programs were collaborative developments, as examples of the potential of learning and adaptation across geographical contexts. It poses two questions: (a) How did the admissions processes in both universities change to target low-SES students? (b) How do social and academic support services for low-SES students, provided by two universities, contribute to the development of student capabilities? The article draws on the capability approach as the evaluative lens used to explore the two programs. Findings indicate (a) innovative approaches to socio-economic assessment in both programs, resulting in effective targeting of low-SES students, (b) the scaling of the programs beyond their initial remit and (c) the emergence of specific student capabilities through their engagement in the programs.